11 Epidemiology of anterior cruciate ligament (ACL) injuries and functional outcomes following rehabilitation in south tees. (13th October 2015) - Akhtar, MA; Olatunbode, O; White, L; Hui, A
Abstract : ACL injury can affect activities of daily living and participation in sports. ACL rehabilitation can improve patient's symptoms. Our aim was to study the epidemiology of ACL injuries and functional outcomes following rehabilitation. Patients undergoing ACL rehabilitation between 2009 and 2014 were identified from a prospective physiotherapy database. Demographic details, number of physiotherapy sessions, length of treatment, discharge destination and functional outcomes were studied. The Knee Injury and Outcome (KOOS) Score and International knee Documentation Committee (IKDC) Score was recorded at the start of rehabilitation and at the last follow up visit. Total number of patients referred for physiotherapy following ACL injuries was 445. 86 (20%) were female and 358 (80%) male with a mean age of 28 y (12–60). The mean number of physiotherapy session was 6 (0–45). The mean length of rehabilitation was 1.6 months (0–14). 98 patients (22%) successfully completed their rehabilitation and were discharged, 93 patients (21%) were listed for surgery, 9 patients (2%) had their care transferred elsewhere and 243 patients (55%) did not attend (DNA) to complete their rehabilitation. The mean KOOS score on referral to physiotherapy was 46 (4–98) and at last follow up was 73 (21–100) with improvement of 27 points. The mean IKDC score was 42 (4.6–81.6) at the start of treatment and 68 (24–100) at the last follow up with improvement of 26 points. There was improvement in functional scores following rehabilitation for the ACL injuries. Only 21% patients underwent ACL reconstruction following their rehabilitation. 55% patients did not attend to complete their rehabilitation. We recommend a flexible rehabilitation programme with the help of written instructions and an open access policy for patients with ACL Injuries. This approach can help to reduce the number of physiotherapy sessions required and also the number of patients who DNA their appointments.